VIOLENCE IN THE MINORS IN THE REPUBLIC OF MACEDONIA (Annual of the Faculty of Philosophy in Skopje, 2012)
In the last decade violent and aggressive behavior in children and young people is increasing steadily. This problem drives more attention to the professional, scientific and general public in Macedonia and abroad.This paper will show the presence of juvenile crime with elements of violence, as well as its structure and distribution by the age of minors in the period between 2001-2010 year in Macedonia.Methods: In this paper is used descriptive method and analysis of official statistics documentations checks for criminal acts committed by 2001-2010 in Macedonia and statistical breakdown of crimes committed in Croatia 2005-2009.Results: According to the results of the analyzed ten year period (2001- 2010) the representation of violent crime among juveniles in Macedonia ranges from 11.4% to 23.4% of the total juvenile crime. The juvenile crime in Croatia for mentioned period is between 20-28% of the total crimes committed.Conclusion:. The volume and dynamics of crime with elements of violence varies and is characterizied by noncontiguous growth in both countries.
Keywords: VIOLENCE; CRIMINAL ACTS; JUVENILES; CRIME, STRUCTURE; DISTRIBUTION